Effects of Dose Wet Fertilizer of Chicken Manure Sediment Water on Abudance of Daphnia magna Population - Sapri Sapri; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABTSRAKThe research was conducted on Agustus, 16th to September, 16th 2018 in the Laboratory of Evironment Quality of Aquaculture, Fisheries and Marine Faculty Universitas of Riau. The objectif of this study research aimed to determine the effects of dose wet fertilizer of chicken manure sedimen water on abudance of Daphnia magnapopulation. This research used experiment method with Completely Randomenzed Design (CRD) one factor (4 level factor) and three replication. The treatment used is giving a dose of fertilizer from sediment water chicken manure with bran; as much 5,5 ml/L (P1), 7,5 ml/L (P2), 9,5 ml/L (P3) and P0 without giving a dose of wet fertilizer. The result of a study showeed that three was influence on the growth of Daphnia magna the population. The treatment was the P1 giving a dose of were fertilizer from sediment water of chicken manure were, 5,5 ml/L (average of 510 ind/L). The water quality condition of this research was still to Daphnia magnaculture; The temperatur, pH, DO, amonia and CO2 (28-29,2 oC, 5,68-6,53, 4,30-5,41 ppm, 0,03-0,193 and 11,82-23,97). The abudance of fhytoplankton obtained from the giving water from green water at the P0 313 ind/L. While in the treatment of giving water from sediment from chicken manure with rice bran; were 5,5 ml/L (P1) 417 ind/L, 7,5 ml/L (P2) 430 ind/L and 9,5 ml/L (P3) 508 ind/L. Key word :Daphnia magna, chicken manure, rice bran.